Navigating Accountability and Sustainability in Accounting Through the Lens of Islamic Ethics - Edgina, Ivahzada Marella; Hamid, Abdul (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
Islamic ethics significantly influences the decision-making processes of accountants, promoting principles of integrity, accountability, and sustainability within financial reporting. This research investigates the importance of Islamic ethical tenets, such as Adl (justice), Sidq (honesty), Amanah (responsibility), and Taqwa (piety), in guiding the professional behavior of accountants. Through a systematic literature review, the study evaluates findings from Scopus-indexed journals and various academic sources to explore the interplay between Islamic ethics, sustainability, and accountability. It highlights prevalent ethical challenges in the accounting field, including financial statement manipulation, insider trading, and conflicts of interest, while also assessing how Islamic ethics can provide solutions to these issues. The results indicate that the integration of Islamic ethics into accounting practices fosters transparency, enhances public trust, and contributes to the sustainability of businesses over the long term. This research underscores the necessity of embedding Islamic ethical principles within accounting regulations, educational frameworks, and professional standards. Additionally, it advocates for further empirical investigations to evaluate the tangible effects of Islamic ethics on corporate governance and financial stability.